Cellular and molecular assessment of rose bengal photodynamic antimicrobial therapy on keratocytes, corneal endothelium and limbal stem cell niche. (November 2019) - Naranjo, Andrea; Pelaez, Daniel; Arrieta, Esdras; Salero-Coca, Enrique; Martinez, Jaime D.; Sabater, Alfonso L.; Amescua, Guillermo; Parel, Jean-Marie
Abstract: Rose Bengal Photodynamic Antimicrobial Therapy (RB-PDAT) is a novel potential treatment for progressive infectious keratitis. The principle behind this therapy is using Rose Bengal as a photosensitizer that can be activated by green light and results in the production of oxygen free radicals which in turn eradicate the microorganism. Given RB-PDAT's mechanism of action and the potential cytotoxic effects, concerns regarding the safety of this technique have arisen. The purpose of this study was to evaluate the effect of RB-PDAT on keratocytes, while focusing on the safety profile that the photo-chemical reaction has on the limbal stem cell (LSC) niche and endothelial cell layer of the treated cornea. To perform RB-PDAT, Rose Bengal solution (0.1% RB in BSS) was applied to the right cornea of rabbits for 30 min and then irradiated by a custom-made green LED light source (525 nm, 6 mW/cm 2 ) for 15 min (5.4 J/cm 2 ). Three rabbits were sacrificed and enucleated after 24 h for evaluation. TUNEL assay and immunohistochemistry for endothelium and limbal stem cell viability were performed on whole mounts and frozen sections in treated and control eyes. LSC of both eyes were isolated and cultured to perform MTT viability and proliferation, and scratch wound healing assays under time-lapse microscopy. Interestingly, while Rose Bengal dye penetration was superficial, yet associated cellular apoptosis was evidenced in up to 1/3 of the stromal thickness on frozen sections. TUNEL assay on whole mounts showed no endothelial cell death following treatment. Immunohistochemistry on frozen sections of LSC displayed no structural difference between treated and non-treated eyes. There was no difference in LSC proliferation rates and scratch wound healing assay demonstrated adequate cell migration from treated and non-treated eyes. The current study suggests that even though penetration of the RB dye has been shown to be limited, oxidative stress produced by RB-PDAT can reach deeper into the corneal stroma. Nevertheless, our results show that performing RB-PDAT is safe on the corneal endothelium and has no effect on LSC viability or function. Highlights: Superficial penetration of the Rose Bengal dye is seen after RB-PDAT. Cellular apoptosis was evidenced in up to 1/3 of stromal thickness. Effects exerted by RB-PDAT penetrate deeper into the corneal stroma than the dye. RB-PDAT is safe on the corneal endothelium. RB-PDAT has no effect on limbal stem cell viability or function.